Conservation genomics of an endangered floodplain dragonfly, Sympetrum pedemontanum elatum (Selys), in Japan - Higashikawa, Wataru; Yoshimura, Mayumi; Nagano, Atsushi J.; Maeto, Kaoru (Conservation genetics, 2024)
Except for fish whose migration is barriered by weirs and dams, there have been inadequate investigation on the population genetic structure of endangered animal species depending on riverside pools connecting to river channels (called “ wando ” in Japanese) in floodplains. We focused on the endangered floodplain dragonfly, Sympetrum pedemontanum elatum, which is known to live in the riverside pools during its larval stage and migrate only several kilometers by flight during adulthood. The population genetic structure in and around the central region of Japan was analyzed using approximately 20,000 SNPs obtained using double-digest restriction site-associated DNA sequencing (ddRAD-seq). Our results revealed small genetic differences over a wide area (global Fst < 0.05). However, a few genetically unique populations that might be associated with paleo-basins segregated during ancient tectonic events were detected. These populations are considered to be important conservation units. We also found a very weak gene flow among the studied populations, implying that population isolation occurs widely. While recent migrations were scarce, and detected within a direct distance of approximately 5 km, there were also some cases without migration, even at shorter distances. Genetic diversity was positively correlated with the amount of grassland within a 1 km buffer, suggesting that the preservation of grasslands surrounding aquatic habitats enhances the immigration and colonization of adult dragonflies of this endangered species. Understanding the effects of historical tectonism and terrestrial environments on the genetic diversity of semi-aquatic organisms, such as insects and amphibians, is crucial for the conservation of floodplain habitat connectivity.